Variability of the Linguistic Consciousness development of an Individual in the Artificial Bilingualism Conditions - Наталя Токарева; Марина Цегельська (Психолінгвістика, 2023)
Purpose. The purpose of this study was to outline the variable markers of the individual linguistic awareness/consciousness development in the conditions of artificial bilingualism.